Pengaruh Surfaktan terhadap Pemisahan Logam Transisi Periode Pertama Menggunakan Metode Emulsion Liquid Membrane - Afifah Rana Widianti; Dwi Ratna Setiani; Fauzia Salsabila; Anni Anggraeni; Uji Pratomo; Husein H. Bahti (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2023)
First row transition metals are heavy metals that are very abundant in their compound form and widely applied in industrial fields because of their unique physical and chemical properties. These industrial activities often produce waste that still contains toxic transition metal. To overcome that problems, the transition metal must be separated by an effective and efficient method, that is the emulsion liquid membrane (ELM) because simultaneous separation process. ELM is a separation method that involves three phases. The determinant of the success of the ELM process is the stability of the emulsion which depends on the concentration and type of the surfactant used. Types of surfactants that can be used in the first row transition metal separation using the ELM method are non-ionic surfactants such as Span 80, a mixture of Span 80-Tween 80 and Polyamine ECA 4360J. Therefore, this review article aims to determine the effect of concentrations and type of that surfactants on emulsion stability and extraction efficiency in the separation of first row transition metals using the ELM method.Keywords: First row transition metals, emulsion liquid membrane, surfactant